Explaining income inequality trends: An integrated approach - Petra Sauer; Narasimha D. Rao; Shonali Pachauri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In large parts of the world, income inequality has been rising in recent decades. Other regions have experienced declining trends in income inequality. This raises the question of which mechanisms underlie contrasting observed trends in income inequality around the globe. To address this research question in a comparative study, we examine a global sample of 73 countries between 1981 and 2010. Yet, we are particularly interested in the heterogeneity of inequality determinants across world regions, and along the income distribution. We find declining labour income shares and increasing imports from high-income countries to significantly contribute to increasing income inequality; taxation and imports from low-income countries exert countervailing effects. The impacts of technological change, financial globalization, domestic financial deepening, and public social spending turn out to be regionspecific. Most importantly, we do not find systematic evidence of education's equalizing effect across high- and low-income countries. Our results are largely robust to changing the underlying sources of income Ginis, but looking at different segments of income distribution reveals heterogeneous effects.
Keywords: I24; O15; O57; 330; comparative study; education; income distribution